A kárpát-medence nyugati-kapuja – Burgenland – a magyar hadtörténelemben = The western gate of the carpathian basin – Burgenland – in hungarian military history - Nagy, Mihály Miklós (Közép-Európai Közlemények, 2018)
Burgenland is located at the western periphery of the Carpathian Basin, and is a province of Austria. It is an artificially created administrative district, not an organically developed historical landscape. However, this region played an important role in Hungarian military history. Its geographical significance in Hungarian military history can be explained by the fact that this region is the Western gateway of the Carpathian Basin. As such, it actually extends beyond the administrative district itself and includes certain areas of Northwestern Hungary as well. The western gateway has been a region with some of the highest landscape energy within the geographical framework of Hungarian military history, which explains its steady role in Hungarian military history in the Carpathian Basin. The western gateway is defined differently in military geography and in political geography, as its boundaries and extent depend on how advanced the contemporary military is and how the military utilizes the landscape. The western gate is a functional space, which is a perfect example for the constant change in the symbiotic relationship of military landscape and military decision-making. The present study provides a definition of the western gateway based on the geography of military history, describes the region’s role during different historical periods, and provides evidence that this role is tightly linked to other regions of the Carpathian Basin with a high geographical value in military history.